2012
DOI: 10.7314/apjcp.2012.13.11.5399
|View full text |Cite
|
Sign up to set email alerts
|

Serum Human Leukocyte Antigen-G and Soluble Interleukin 2 Receptor Levels in Acute Lymphoblastic Leukemic Pediatric Patients

Abstract: Aims and Background: Human leukocyte antigen-G and interleukin-2 receptor play pivotal roles in the proliferation of lymphocytes, and thus generation of immune responses. Their overexpression has been evidenced in different malignant hematopoietic diseases. This study aimed to validate serum soluble human leukocyte antigen-G (sHLA-G) and serum soluble interleukin-2 receptor (sIL-2R) as an additional tool for the diagnosis and follow up of acute lymphoblastic leukemia (ALL). Subjects and Methods: Both markers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…All these results suggest that H2S and cytokines are involved in immune regulatory process of children with ALL with chemotherapy, which is consistent with this report. Motowi et al [ 17 ] suggested that measurement of serum sHLA-G might be helpful in diagnosis of ALL, while sIL-2R might be useful in diagnosis and follow-up of ALL in paediatric patients. Research carried out in order to search for new more effective treatments for patients with ALL, seems inclined to use the immune response factors, such as NK in the presence of clinical grade IL-2 and IL-15 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these results suggest that H2S and cytokines are involved in immune regulatory process of children with ALL with chemotherapy, which is consistent with this report. Motowi et al [ 17 ] suggested that measurement of serum sHLA-G might be helpful in diagnosis of ALL, while sIL-2R might be useful in diagnosis and follow-up of ALL in paediatric patients. Research carried out in order to search for new more effective treatments for patients with ALL, seems inclined to use the immune response factors, such as NK in the presence of clinical grade IL-2 and IL-15 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of ALL cases have class I MHC expression . In addition, non‐classical HLA‐G was up‐regulated after chemotherapy treatment . No significant differences in MHC class I expression were seen between diagnostic and relapsed samples in pre‐B ALL .…”
Section: Mhc Class I Expression In Pediatric Tumorsmentioning
confidence: 94%
“…The majority of ALL cases have class I MHC expression . In addition, non‐classical HLA‐G was up‐regulated after chemotherapy treatment .…”
Section: Mhc Class I Expression In Pediatric Tumorsmentioning
confidence: 99%